Ionomer Membranes Produced from Hexaarylbenzene-Based Partially Fluorinated Poly(arylene ether) Blends for Proton Exchange Membrane Fuel Cells - Tzu-Sheng Huang; Hsin-Yi Wen; Yi-Yin Chen; Po-Hao Hung; Tung-Li Hsieh; Wen-Yao Huang; Mei-Ying Chang (Membranes, 2022)
In this study, a series of high molecular weight ionomers of hexaarylbenzene- and fluorene-based poly(arylene ether)s were synthesized conveniently through condensation and post-sulfonation modification. The use a of blending method might increase the stacking density of chains and affect the formation both of interchain and intrachain proton transfer clusters. Multiscale phase separation caused by the dissolution and compatibility differences of blend ionomer in high-boiling-point solvents was examined through analysis and simulations. The blend membranes produced in this study exhibited a high proton conductivity of 206.4 mS cm−1 at 80 °C (increased from 182.6 mS cm−1 for precursor membranes), excellent thermal resistance (decomposition temperature > 200 °C), and suitable mechanical properties with a tensile strength of 73.8–77.4 MPa. As a proton exchange membrane for fuel cell applications, it exhibits an excellent power efficiency of approximately 1.3 W cm−2. Thus, the ionomer membranes have strong potential for use in proton exchange membrane fuel cells and other electrochemical applications.